Owl Ways / Joydee Ambrose ... [et al.] - Ambrose, Joydee; Berahim, Haleeda; Abdullah, Mohd Sharul Izam; Erison, Erzianty; Abdul Rahim, Siti Hajar (2014)
This business is based on partnership where it consists of five (5) members which hold important positions in the company such as General Manager, Administrative Manager, Marketing Manager, Financial Manager and Operation Manager. The business capital is amounted to RM50 000 where the total contribution of each member is RM10000 and the rest RM 50 000 is from Bank Islam's Loan. Serving fast food for everyone especially family with our special menu, being made with different types of bread and tortilla wraps with the combination taste between meat and vegetables. Owl Ways Enterprise with tagline 'Family "Owl Ways" Together is located at Kota Kinabalu with address Lot C-778A, 1Bomeo HyperMall, Jalan Sulaman, 88400 Kota Kinabalu, Sabah, Malaysia. Owl Ways is a company that focuses on family that love to eat fast food, which is being innovated by our very own ideas. The taste of our food brought happiness toward our customers, instead of having a great taste it is also healthy when comparing to other fast food. Moreover, the simple steps and ingredients give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting we also making some innovation by implying our creativity. Healthy food are important to everyone, by comparing to others fast food restaurant our company are healthier. Therefore, it are suitable for every level of ages and our packaging are also easy and simple that everyone can hold it and bring it everywhere.